PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN DISIPLIN KERJA TERHADAP KOMPETENSI GURU DENGAN MOTIVASI BERPRESTASI SEBAGAI VARIABEL MODERASI - Lestari, Siti -; -, Sutarno - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The expected goal of this research are to: (1) analyze the significance of the influence of the principal's leadership on teacher competence, (2) analyze the significance of the influence of labor discipline on the competence of teachers, (3) analyze the significance of the effect of achievement motivation on teacher competence, (4) analyzing the significant influence achievement motivation in moderating the influence of principal leadership on teachers' competence, and (5) analyze the significance of achievement motivation in moderating the influence of labor discipline on teacher competence. The study population was all civil servants in the state primary school teachers Gondangrejo Karanganyar District. Research sample 84 respondents with sampling proportional random sampling. Types of data using qualitative data and quantitative data. Sources of data using primary data and secondary data. Techniques of data collection using interviews and questionnaires. The analysis technique uses test validity, test reliability classical assumption test, linear regression, t test, F test, the coefficient of determination and absolute difference test. The results showed: (1) the principal's leadership has a significant effect on teacher competence, (2) work discipline has a significant impact on teacher competence, (3) achievement motivation has a significant effect on teacher competence, (4) achievement motivation moderate the effect of principal leadership on teachers' competence, (5) moderate the influence of achievement motivation work discipline to teacher competence. Keywords: principal leadership, work discipline, achievement motivation, teacher competence